VALUING OF USEFULNESS OF THE MILKING COWS TO BECOME DONORSRECEPIENTS OF THE BEFORE-IMPLANTANT EMBRYOS - Сідашова, С. О. (Scientific Progress & Innovations, 2013)
We have adducted the results of the examination by touch of the morphofunctional condition of dairy cow ovary and luteogenesis for the selection of the animals with the aim of embryodonation. In 9- 14% of the cows we have seen deficiency in the formation of luteal state from the 5th till the 15th day because of the absence of the development in ovary a yellow body .Also 17-43% of them were unable for embryodonation because of the kistosis degenerations of the follicle: the embryos flushed out of them on the 7th-8th day after polyovulation had deep morphological defects and were lacking vitality.